The compliance of our practice of hepatitis B virus screening with the current guidelines in patients undergoing chemotherapy for hematological malignancies - Pepedil Tanrikulu, Funda; Yanardağ Açık, Didar; Aygun, Bilal; Bankir, Mehmet; Özdemir, Mikail (Journal of Surgery and Medicine, 2021)
Background/Aim: The reactivation of Hepatitis B virus (HBV) among cancer patients is a critical issue which is preventable by precise detection of risky cases prior to the administration of chemotherapy drugs. This study aimed to investigate whether the evaluated serological tests for HBV screening before chemotherapy in adults with newly diagnosed hematological malignancies follow the guidelines. Methods: In this retrospective cohort study, all patients with hematological malignancies who visited our hematology clinic between January 01, 2018-January 01, 2020, were examined and adult patients referred to the outpatient clinic for combined chemotherapy were included. All clinical data and laboratory results were obtained from the electronic hospital information system. Serological tests performed for HBV screening and their results were noted. The compliance of our clinical practice with the current guidelines was analyzed assuming that there are three mandatory serological tests for screening, HBsAg, anti-HBs and anti-HBc, recommended in the guidelines. Results: A total of 91 newly diagnosed cases were included for analysis. HBV screening completely lacked in 10% of the patients and it did not follow the current guidelines in 30%. The most neglected serological test was anti-HBc. Regarding different hematological malignancies, the results were best in lymphoma patients (76% compliance with guidelines) and worst in MM (only 40% compliance with guidelines). The serological test results of eighty-two cases were also examined and the seropositivity rates for HBsAg and anti-HBc were 2%, and 41%, respectively. Conclusion: We observed that the risk of reactivation was not adequately evaluated by serological screenings for HBV in adult patients receiving chemotherapy for hematological malignancy. To protect patients from this mostly preventable complication, it is necessary to increase the awareness on the subject and encourage more compliance with the related guidelines.